2021
DOI: 10.7717/peerj.11131
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on admission trends of Californian hummingbirds found in urban habitats (1991–2016)

Abstract: Background Hummingbirds are frequently presented to California wildlife rehabilitation centers for medical care, accounting for approximately 5% of overall admissions. Age, sex, and reason for admission could impact hummingbird survivability, therefore identification of these factors could help maximize rehabilitation efforts. Methods Mixed-effects logistic regression models were used to identify specific threats to the survival of 6908 hummingbirds (1645 nestlings and 5263 non-nestlings) consisting of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Alternatively, parental loss accounted for far more mammalian WRC admissions than birds and other species. Those admitted because they were found in unsuitable locations were most commonly birds as well as amphibians and mammals, as reported by others (Dubois 2003;Wimberger and Downs 2010;Pandit et al 2021). Nest or habitat disturbances were common for hares and rabbits, reptiles, and amphibians.…”
Section: Other Situations and Human-wildlife Conflictmentioning
confidence: 61%
See 1 more Smart Citation
“…Alternatively, parental loss accounted for far more mammalian WRC admissions than birds and other species. Those admitted because they were found in unsuitable locations were most commonly birds as well as amphibians and mammals, as reported by others (Dubois 2003;Wimberger and Downs 2010;Pandit et al 2021). Nest or habitat disturbances were common for hares and rabbits, reptiles, and amphibians.…”
Section: Other Situations and Human-wildlife Conflictmentioning
confidence: 61%
“…Across Canada, trauma was the most common cause of CWHC mortality and WRC admission, overwhelmingly due to vehicle and window collisions and attacks by cats (Tables 2 and 3). This was expected given that numerous studies have also identified collisions and cats as the main sources of trauma for North American wildlife (Hartup 1996;Dubois 2003;Loss et al 2015;Long et al 2020;Pandit et al 2021). Cats have been shown to have devastating effects on bird and mammal populations (Loss et al 2013).…”
Section: Traumamentioning
confidence: 98%
“…In the expanded ranges C. anna individuals were more likely to colonize areas with higher housing density and were more likely to visit bird feeders compared to those in the historical range (Greig et al, 2017). However, like many North American migratory birds, they may also experience mortality associated with urban settings such as window collisions and encounters with domesticated animals (Pandit et al, 2021). Increases in minimum winter temperatures were also shown to facilitate the expansion (Battey, 2019; Greig et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, like many North American migratory birds, they may also experience mortality associated with urban settings such as window collisions and encounters with domesticated animals (Pandit et al, 2021). Increases in minimum winter temperatures were also shown to facilitate the expansion (Battey, 2019;Greig et al, 2017).…”
mentioning
confidence: 99%